(untitled) (Journal of Global Arts Studies, 2024)
Background: Since the United Nations proposed the Child-Friendly Cities Initiative, the construction of urban public spaces has attracted more and more attention. Urban families have an increasing demand for urban public spaces that are safe, healthy and educational. Parents expect such spaces to promote the development of children’s cognitive, emotional and social skills. Objective: Explore how to effectively integrate educational elements into urban public spaces, provide scientific basis and practical suggestions for urban planning and design, and build a more child-friendly urban environment. Methods: The study used literature analysis and survey methods to conduct in-depth field investigations on urban public spaces such as community parks, science and technology museums, libraries, and children’s playgrounds in Wuhan, to identify the degree of support for children’s educational functions in existing urban public spaces, as well as deficiencies in design and management. Results: Educational elements in urban public spaces can effectively promote the development of children’s cognitive, emotional and social skills. Such spaces not only provide a safe place to play, but also realize educational functions in a subtle way. Conclusion: Urban public spaces play an important role in children’s education and family interaction and are an indispensable part of modern cities. Governments and urban planners should attach importance to their construction and maintenance, formulate relevant policies and standards, and encourage more urban public spaces with educational functions to be implemented in cities.